Fundamentals of Entrepreneurship (ENT 300) Business Plan: Rifa Florist Shop / Nur Afifah Yaacob - Yaacob, Nur Afifah (2019)
RIFA florist shop is a retail establishment that sells cut flowers and ornamental plants that along with online stores. The floral trade involves activities such as flower care, flower arranging, floral design, and often flower delivery. Florist shops are an ever popular industry nowadays.